2019
DOI: 10.1101/627240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial mass governs the extent of T cell senescence

Abstract: The susceptibility of human CD4+ and CD8+ T cells to senesce differs, with CD8+ T cells acquiring an immunosenescent phenotype faster than the CD4+ T cell compartment. We show here that it is the inherent difference in mitochondrial content that drives this phenotype, with senescent human CD4+ T cells displaying a higher mitochondrial mass. The loss of mitochondria in the senescent human CD8+ T cells has knock‐on consequences for nutrient usage, metabolism and function. Senescent CD4+ T cells uptake more lipid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This phenotype may be indicative of T cell exhaustion and is typically observed in chronic viral infection (463). Increased mitochondrial mass: Suggests impaired mitochondrial and glycolytic metabolism in ME/CFS T cell subsets (464).…”
Section: Reduced Mitochondrial Membrane Potentialmentioning
confidence: 99%
“…This phenotype may be indicative of T cell exhaustion and is typically observed in chronic viral infection (463). Increased mitochondrial mass: Suggests impaired mitochondrial and glycolytic metabolism in ME/CFS T cell subsets (464).…”
Section: Reduced Mitochondrial Membrane Potentialmentioning
confidence: 99%
“…Indeed, we have shown that human CD8 + T cells were more susceptible to senescence compared to their CD4 + counterparts as they displayed a lower mitochondrial content and postulated loss of mitochondrial function controls the senescence phenotype in T cells [4] as well as other cell types [5,6]. However the mechanism remained elusive, that is until the recent paper by Desdin-Mico et al published in Science demonstrated that mitochondrial dysfunction was controlled by mitochondrial transcription factor A (TFAM) [7].…”
mentioning
confidence: 99%